2011
DOI: 10.1007/s11250-011-9811-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ventilation of the sheep house on heat stress, growth and thyroid hormones of lambs

Abstract: Twenty single male Assaf lambs were divided into two groups and housed in semi-open barns. Air temperature averaged 35°C. For 9 weeks after parturation, one group was cooled by fan between 1000 and 1600 hours and the other group was not cooled. Rectal and skin (head and testis) temperatures, respiration rate, and pulse rate were recorded twice daily. Lambs were weighed individually every week and levels of T3 and thyroxin were determined. Differences in rectal, head, and testis temperatures (P<0.05) and respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 14 publications
5
29
0
Order By: Relevance
“…Several studies pointed out that animals decrease T 4 secretions when environmental conditions are stressful as a way of reducing endogenous heat, yet this hormone has a high thermogenic activity (Clarke et al 1997;Veríssimo et al 2009). Al-Haidary (2004), Starling et al (2005), Maurya et al (2010) and Koluman and Daskiran (2011) also found significant reductions in thyroid hormones as a response to high air temperature.…”
Section: Resultsmentioning
confidence: 93%
“…Several studies pointed out that animals decrease T 4 secretions when environmental conditions are stressful as a way of reducing endogenous heat, yet this hormone has a high thermogenic activity (Clarke et al 1997;Veríssimo et al 2009). Al-Haidary (2004), Starling et al (2005), Maurya et al (2010) and Koluman and Daskiran (2011) also found significant reductions in thyroid hormones as a response to high air temperature.…”
Section: Resultsmentioning
confidence: 93%
“…According to Todini (2007) the major exogenous regulator of thyroid gland activity is the environmental temperature, so an inverse relationship between ambient temperature and blood T 3 and T 4 concentrations can be expected in sheep under hot weather conditions. Lower serum levels of T 3 in hot environments can be expected due to the decisive role of T 3 and T 4 in thermogenesis, energy and proteins metabolism, as well as in metabolic responses of the animals to different nutritional and environmental changes (KOLUMAN; DASKIRAN, 2011). The fall in T 3 concentrations was greater in red ewes, compared with the white colored ones maybe can be due to the higher absorption of solar radiation.…”
Section: Discussionmentioning
confidence: 99%
“…These hormones are directly involved with metabolic rate regulation and obligatory thermogenesis, thus they have an essential role in thermoregulation and homeothermy. Koluman and Daskiran (2011) observed a reduction in the serum concentrations of thyroid hormones in sheep exposed to high temperatures, maybe to reduce the basal metabolic rate and avoiding an increase in endogenous heat production. The variation in concentrations of thyroid hormones can be high, and genetic factors may cause different responses, influencing the degree of adaptability to climatic stressors.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Cattle need to maintain a constant body temperature (38.8 ± 0.5 °C) in order to sustain body physiologic balance. Environmental factors such as temperature, humidity and air velocity, influence cattle thermal balance [23,24]. When beef barns are planned, all these climatic environmental factors are taken into consideration and the animal's requirements are tried to be met.…”
Section: Barn Environment Controlmentioning
confidence: 99%